1998
DOI: 10.1111/j.1095-8649.1998.tb00967.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of phospholipid and fatty acid composition of wild and cultured striped bass eggs

Abstract: The dominant fatty acids in all neutral lipid fractions of non-water hardened eggs from two wild and one cultured stock of striped bass Morone saxatilis were the monoenes, 18 : 1n9/ n7>16 : 1n7>17 : 1. The dominant fatty acids in the phospholipid fraction of all eggs, regardless of origin, were 22 : 6n3>18 : 1n9/n7>20 : 5n3>16 : 1n7>16 : 0>18 : 0. Arachadonic acid (AA, 20 : 4n6) was significantly lower (2·0%) in cultured fish eggs compared to either wild stock (5·8-6·1%). Fatty acids from the liver and eggs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 29 publications
3
15
1
Order By: Relevance
“…Eggs from field-collected striped bass were slightly larger and in 1 year (1999) had slightly higher total lipid than the hatchery controls. Other studies have reported similar findings, indicating that river-collected striped bass eggs were of higher quality than hatchery eggs (18,19).…”
Section: Resultssupporting
confidence: 69%
“…Eggs from field-collected striped bass were slightly larger and in 1 year (1999) had slightly higher total lipid than the hatchery controls. Other studies have reported similar findings, indicating that river-collected striped bass eggs were of higher quality than hatchery eggs (18,19).…”
Section: Resultssupporting
confidence: 69%
“…Eggs from cultured Atlantic salmon had an increased level of 20:5n-3 and a decreased level of 20:4n-6 which greatly increased the ratio of 20:5n-3 : 20:4n-6 in the cultured eggs as compared to wild eggs (Pickova et al, 1999). Decreased 20:4n-6 in eggs from cultured fish in comparison with wild fish was also observed in striped bass (Gallagher et al, 1998). In contrast, the above study with…”
Section: Functionscontrasting
confidence: 51%
“…The polar lipids of most fish eggs are dominated by phosphoglycerides, particularly PtdCho, followed by PtdEtn, PtdSer and PtdIns. Exceptions to this pattern are striped bass eggs, whose phospholipids are reported to contain predominantly PtdIns (Gallagher et al, 1998), and sturgeon eggs, which have relatively high PtdEtn (Gershanovich, 1991). The neutral lipids are mainly triacylglycerols with smaller amounts of cholesterol although some lipid -rich eggs have globules that are predominantly steryl and/or wax esters as in gourami or some freshwater Perciformes and striped bass (Anderson et al, 1990;Wiegand, 1996a).…”
Section: Functionsmentioning
confidence: 99%
“…Others have reported that 18:1n-9 is the most common fatty acid in sturgeon and other fish eggs and tissues [6,26,[29][30][31][32][33]. The results of this study show that MUFAs were higher in wild than in domestic beluga.…”
Section: Fatty Acid Profile Chemical Composition and Fertilization Rsupporting
confidence: 46%
“…The amount of linoleic acid (18:2n-6) was much greater in the cultivated beluga eggs than in wild ones. The same tendency was also found in the lipid profile of ovulated eggs of wild and cultured turbot (Scophthalmus maximus) [30], striped bass (Morone saxatilis) [32] and white sturgeon [6] and is a reflection of dietary fat intake [2,6,11,30]. In addition, Hosseini et al [33] compared the effect of three different diets including fish oil, soybean oil and canola oil on muscle fatty acids profiles in cultivated beluga (H. huso).…”
Section: Fatty Acid Profile Chemical Composition and Fertilization Rmentioning
confidence: 69%